2020
DOI: 10.1371/journal.pone.0238095
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between proinsulin, true insulin, proinsulin: True insulin ratio, 25(OH) D3, waist circumference and risk of prediabetes in Hainan Han adults

Abstract: Diabetes mellitus is a kind of highly prevalent chronic disease in the world. The intervention measures on the risk factors of prediabetes contribute to control and reduce the occurrence of diabetes. This study aimed to investigate the correlation between proinsulin (PI), true insulin (TI), PI/TI, 25(OH) D3, waist circumference (WC), and risk of prediabetes. Methods In this cross-sectional study, 1662 subjects including 615 prediabetes and 1047 non-prediabetes were recruited. Spearman's correlation analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…WC is considered to be one of the strongest risk factors for prediabetes. 58 It is also considered to be better than BMI for determining the risk of diabetes 43 although ADA guidelines suggest using BMI≥25 kg/m 2 criteria for screening diabetes for asymptomatic undiagnosed adults. 1 In the present study, WC was measured for all screened participants as it was one of the parameters of IDRS, 30 and weight and height were measured only for participants with prediabetes during their detailed data collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WC is considered to be one of the strongest risk factors for prediabetes. 58 It is also considered to be better than BMI for determining the risk of diabetes 43 although ADA guidelines suggest using BMI≥25 kg/m 2 criteria for screening diabetes for asymptomatic undiagnosed adults. 1 In the present study, WC was measured for all screened participants as it was one of the parameters of IDRS, 30 and weight and height were measured only for participants with prediabetes during their detailed data collection.…”
Section: Discussionmentioning
confidence: 99%
“…WC is considered to be one of the strongest risk factors for prediabetes 58. It is also considered to be better than BMI for determining the risk of diabetes43 although ADA guidelines suggest using BMI≥25 kg/m 2 criteria for screening diabetes for asymptomatic undiagnosed adults 1.…”
Section: Discussionmentioning
confidence: 99%
“…Manning et al also observed that 6 SNPs in COBLL1-GRB14, IRS1, PPP1R3B, PDGFC, UHRF1BP1, and LYPLAL1 are correlated with the FI level [19]. However, those SNPs explained only were associated with an increased risk of prediabetes [13]. Despite these findings, it is still unclear how these common phenotypes affect T2DM.…”
Section: Discussionmentioning
confidence: 99%